Attitudes of Postgraduate Students Towards Distance Education During the COVID-19 Pandemic: North Cyprus Example - Aksoy, Yeşim Üstün (Frontiers in Psychology, 2021)
The distance education model has become the most common educational model used around the world due to the COVID-19 pandemic that emerged in China at the end of 2019. In North Cyprus (NC), traditional face-to-face education had been resumed through online channels. The rapid shift to online channels has not only caused distress among students who do not have experience with using in online education systems, but also caused many problems to surface in terms of access to education. This study aims to explore the attitudes and views of higher education students in NC regarding the distance education implemented during the COVID-19 pandemic in the 2020–2021 educational year. In this quantitative study, the survey method was used. A random sampling approach was used for determining the study group, which was formed of 470 volunteer higher education students. According to the analysis of the data collected from the students, it was determined that they received an average score of x̅=82.52±19.50 points from the overall Attitudes Regarding the Use of Distance Education Environments During the Pandemic (ASRUDEEDP) scale, x̅=23.03±7.21 from the competence and education sub-dimension, x̅=26.36±5.81 from the practicality sub-dimension, x̅=18.20±4.83 points from the efficiency sub-dimension, and x̅=14.93±4.12 from the satisfaction sub-dimension. It was identified that there were no differences in the scores according to the age group, grade, or Internet use durations (p>0.05) but the scores of male students were observed to be higher than those of female in the sub-dimensions of competence and motivation as well as practicality within the ASRUDEEDP.